Risk and Crisis Communication: When Things Go Wrong - Ricky Telg (EDIS)
WC093, a 9-page illustrated fact sheet by Ricky Telg, examines the practice of crisis and risk communication as part of an organization’s overall crisis plan. Includes references. Published by the UF Department of Agricultural Education and Communication, July 2010.